Digital Accounting Use and Perceived MSME Performance: Mediating Roles of Perceived Financial Reporting Quality and Financial Literacy - Agustina; Vina Winda Sari (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study examines whether Digital Accounting Use improves Perceived MSME Performance and whether Perceived Financial Reporting Quality and Financial Literacy operate as parallel mediating capabilities among current users of digital financial-recording tools. Methods - A quantitative cross-sectional explanatory design was applied to 200 MSME owners and managers in five economic centers of North Sumatra, Indonesia. The respondents were purposively selected because their businesses already used at least one digital financial-recording tool. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to evaluate the measurement and structural models. Findings - Digital Accounting Use significantly increased Perceived Financial Reporting Quality (β = 0.788, p < 0.001), Financial Literacy (β = 0.771, p < 0.001), and Perceived MSME Performance (β = 0.565, p < 0.001). Perceived Financial Reporting Quality (β = 0.493, p = 0.002) and Financial Literacy (β = 0.326, p = 0.025) also positively affected Perceived MSME Performance. The indirect effects through Perceived Financial Reporting Quality (β = 0.445, p < 0.001) and Financial Literacy (β = 0.252, p = 0.028) were significant, indicating partial mediation. The model explained 73.3% of the variance in Perceived MSME Performance (R² = 0.733). Research implications - MSME digitalization programs should combine sustained use of accounting technologies with reporting discipline and financial-literacy development so that technological resources are converted into decision-useful information and managerial capability. Originality - The study advances a post-adoption capability perspective by separating the informational pathway of Perceived Financial Reporting Quality from the human-capability pathway of Financial Literacy and testing both mechanisms simultaneously.